American literature : themes and writers - Carlsen, G. Robert, 1917-; Schuster, Edgar Howard, 1930-; Tovatt, Anthony (New York : Webster Division, McGraw-Hill, 1973)
A thematically arranged anthology of poems, short stories, plays, novellas, and excerpts from longer works by American authors for the eleventh-grade reader.
Keywords: American literature; American literature -- Themes, motives; American literature -- Collections; United States -- Civilization -- Literary collections